2015
DOI: 10.1016/j.jsbmb.2014.11.016
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D3 induces monocytic differentiation of human myeloid leukemia cells by regulating C/EBPβ expression through MEF2C

Abstract: Myogenic enhancer factor2 (Mef2) consists of a family of transcription factors involved in morphogenesis of skeletal, cardiac and smooth muscle cells. Among the four isoforms (Mef2A, 2B, 2C, and 2D), Mef2C was also found to play important roles in hematopoiesis. At myeloid progenitor level, Mef2C expression favors monocytic differentiation. Previous studies from our laboratory demonstrated that ERK5 was activated in 1,25-dihydroxyvitamin D3 (1,25D)-induced monocytic differentiation in AML cells and ERK5 activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
(50 reference statements)
2
19
0
Order By: Relevance
“…We evaluated the effect of p , p ′ - DDE on intracellular molecules that are involved in activation of C/EBP β , a transcription factor activated during myeloid differentiation [3032]. Our results demonstrate that p , p ′ - DDE induced an increase in nuclear levels of C/EBP β , an effect that was dependent on p38 activation and is consistent with data previously reported [52].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We evaluated the effect of p , p ′ - DDE on intracellular molecules that are involved in activation of C/EBP β , a transcription factor activated during myeloid differentiation [3032]. Our results demonstrate that p , p ′ - DDE induced an increase in nuclear levels of C/EBP β , an effect that was dependent on p38 activation and is consistent with data previously reported [52].…”
Section: Discussionsupporting
confidence: 87%
“…CCAAT/enhancer binding protein β (C/EBP β ) is involved in gene expression and regulates differentiation in haematopoietic cells [29]. C/EBP β expression is induced in myeloid progenitors when emergency granulopoiesis is required and during monocyte differentiation [3032]. Its function is regulated by posttranslational modifications including phosphorylation [33].…”
Section: Introductionmentioning
confidence: 99%
“…However, further studies have generated controversial and unclear results. Recently, ERK5 was shown to be involved in the monocytic differentiation of human AML cells upon cell treatment with 1,25D vitamin D3 [68]. In agreement with this study, others demonstrated that, in human AML cells, both established cultures and AML blasts ex vivo, ERK5 directly promoted the optimal monocytic differentiation of AML cells when exposed to differentiating agents [65].…”
Section: Leukaemiasupporting
confidence: 81%
“…Increased mRNA levels of both CD11b and CD14 markers in AML blasts, though modest, suggested monocytic type of differentiation (Figure 3A). This was supported by the increased expression of the C/EBPβ transcription factor (TF), linked to signaling of monocytic differentiation [28] in AML blasts, but not in non-differentiating normal bone marrow cells treated in the same way (Figure 3B). Similarly, the expression of the vitamin D-regulated TF VDR was found to be enhanced at mRNA and protein levels by the AraC-D2/CA combination (Figure 3C and 3D).…”
Section: Resultsmentioning
confidence: 89%